Difficult Conditions in Laparoscopic Urologic Surgery (Springer International Publishing, 2018)
This book outlines potential situations faced by those using laparoscopy and provides solutions for difficult conditions. Extensively and thoroughly written by experts in the field, Difficult Conditions in Laparoscopic Urologic Surgery enables the practising surgeon to confront and resolve dilemmas before even entering the operating theatre. In this book, every urologic procedure is described using a step-by-step sequence of events and the text is supplemented with numerous tips, illustrations, and high definition photographs depicting the main steps of the procedures. With a problem-oriented approach, Difficult Conditions in Laparoscopic Urologic Surgery is a valuable reference source for residents, fellows, and general urologists. .